KONTRIBUSI SEKTOR PERTANIAN DALAM PEREKONOMIAN WILAYAH KABUPATEN PATI - Eka Dewi Nurjayanti (Universitas Wahid Hasyim, 2012)
The purpose of this research are to identify the economic sector and agriculture sub sector, to analyze the position changes of economic sector and agriculture sub sector in Purworejo Regency. The research method used is descriptive method, which employs the data analysis method of Location Quotient (LQ), Dynamic Location Quotient (DLQ) and merger of LQ and DLQ. This research takes the Gross Domestic Regional Product (GDRP) of Central Java Province and Pati Regency for the Basic Price Occur period of 2008-2011 and Pati Regency in Figures 2011, as the data. The result of this research shows that during four years (2008-2011), Pati Regency posseses three economic sectors which become the base sector, there are agriculture sector, electric, gas and clear water sector, and services sector. While the base sector of agriculture sub sector are plant producing food sub sector, plantation, forestry and fishery sub sector. According to DLQ analysis, there are seven economic sectors and three agriculture sub sectors that may become the base sector in the future. The third of economic sectors are agriculture sector, electric, gas and clear water sector, and services sector, while for the agriculture sub sectors are plant producing food sub sector, plantation, and fishery sub sector. The economic sector of Pati Regency which experience the position changes in the future are building and construction sector. The agriculture sub sector of Pati Regency which the experience the position changes in the future are forestry sub sector. Keywords: agriculture, Location Quotient, Dynamic Location Quotient